Comprensión de textos escritos en estudiantes de quinto grado de secundaria en instituciones educativas urbanas y rurales del distrito de Nauta 2022 - Ahuanari Tamani, Armando (2023)
This study main objective was to compare fifth year students’ reading skills between rural and urban secondary schools in Nauta district 2022. The research type was comparative with field study, contemporary transectional, and univariate designs. The study population was 622 students and a stratified sample with proportional affixation of 328 students. The data gathering tool was a valid and reliable reading comprehension test. Results show that the 8 urban school students’ mean score was higher than those of the 24 rural school students’ (6,536>5,849). In conclusion, Mann-Whitney’s U test showed that there is statistically significant difference in reading performance between the two groups, as p-value = 0,042 < ? = 0,05.